1993
DOI: 10.1002/bdd.2510140703
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between content of hepatic glutathione S‐transferases and the kinetics of indocyanine green elimination in various liver diseases

Abstract: The glutathione (GSH) S-transferases are believed to have dual functions as hepatic detoxifying enzymes and intrahepatic binding proteins. Little is known about their alterations in human liver diseases. Therefore, we have studied the relationship between the enzyme activity and rose bengal (RB) binding in hepatic cytosol and plasma indocyanine green (ICG) kinetics in patients with various liver diseases. The enzyme activity was measured in samples of hepatic cytosol obtained from 52 patients. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…An example is indocyanine green, a photosensitizer which is directly bound to glutathione-S-transferases. [50] …”
Section: Combined Gene-dose Effects and Gst Gene-equivalentsmentioning
confidence: 97%
“…An example is indocyanine green, a photosensitizer which is directly bound to glutathione-S-transferases. [50] …”
Section: Combined Gene-dose Effects and Gst Gene-equivalentsmentioning
confidence: 97%
“…The combination of a very high level expression of GSTs in several tumor cells and normal tissues and high affinity binding suggests the possibility that HYP uptake by cells could be affected by GST expression. Indeed, it has been suggested that cellular uptake and localization of hematoporphyrin and indocyanine dyes are altered by expression of, and binding to, GSTs ( ).…”
Section: Discussionmentioning
confidence: 99%